2003
DOI: 10.1001/archotol.129.1.106
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Head and Neck Squamous Cell Carcinoma in Patients With Fanconi Anemia

Abstract: In patients with FA, there is a high incidence of aggressive HNSCC at a young age. Surgery remains the mainstay of treatment because patients with FA tolerate radiation therapy and chemotherapy poorly, with significant morbidity. An increased understanding of FA-associated malignancies is not only important in the clinical management of patients with FA but can also elucidate the role of chromosomal instability in the development of HNSCC in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
315
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(334 citation statements)
references
References 32 publications
17
315
0
2
Order By: Relevance
“…Furthermore, despite the mild course of her disease, the patient experienced two different episodes of malignancy (esophageal carcinoma and gingival in situ carcinoma), thus underlining the high propensity of cancer development in such patients [6]. As in the present case, malignancy recurrence in FA patients is often a significant issue as shown in the prospective study by Kutler et al, who found that among the 19 FA patients who developed SCC, 10 (53%) developed locoregional recurrences within a median of 16 months after diagnosis [11]. In this patient, recurrence occurred 26 months after the first gingival SCC diagnosis.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, despite the mild course of her disease, the patient experienced two different episodes of malignancy (esophageal carcinoma and gingival in situ carcinoma), thus underlining the high propensity of cancer development in such patients [6]. As in the present case, malignancy recurrence in FA patients is often a significant issue as shown in the prospective study by Kutler et al, who found that among the 19 FA patients who developed SCC, 10 (53%) developed locoregional recurrences within a median of 16 months after diagnosis [11]. In this patient, recurrence occurred 26 months after the first gingival SCC diagnosis.…”
Section: Discussionsupporting
confidence: 59%
“…FA patients who are homozygous for mutation of a FA gene have a systemic DNA repair defect that results in a low tolerance for DNA-damaging chemotherapeutic agents. Accordingly chemotherapeutic agents are often given at low dosage or are avoided in favor of surgical approaches (Kutler et al 2003a). The situation, however, is different for cancer patients who carry a heterozygous mutation in a FA gene.…”
Section: The Fa Pathway and Cancer Treatmentmentioning
confidence: 99%
“…These patients, who inherit recessive autosomal mutations in genes regulating DNA recognition and repair, show an increased risk of bone marrow failure, leukemia, and solid tumors including OSCC. Fanconi anemia patients have a 500-to 700-fold increased risk of OSCC formation [23][24][25][26]. Increased risk of OSCC has also been reported in individuals inheriting functionally inactivating mutations in the CDKN2A gene.…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%